Impact of sodium vanadium oxide (NaV3O8, NVO) material synthesis conditions on charge storage mechanism in Zn-ion aqueous batteries. Issue 14 (26th March 2021) - Tang, Christopher R.; Singh, Gurpreet; Housel, Lisa M.; Kim, Sung Joo; Quilty, Calvin D.; Zhu, Yimei; Wang, Lei; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Marschilok, Amy C.
Abstract : The electrochemical charge storage of sodium vanadate (NaV3 O8 or NVO) cathodes in aqueous Zn-ion batteries is influenced by post-synthesis heat treatment that alters rate and amount of ion transfer in the material. Abstract : The electrochemical charge storage of sodium vanadate (NaV3 O8 or NVO) cathodes in aqueous Zn-ion batteries has been hypothesized to be influenced by the inclusion of structural water for facilitating ion transfer in the material. Materials properties considered important (morphology, crystallite and particle size, surface area) are systematically studied herein through investigation of two NVO materials, NaV3 O8 ·0.34H2 O [NVO(300)] and NaV3 O8 ·0.05H2 O [NVO(500)], with different water content, acicular morphologies with different size and surface area achieved via post-synthesis heat treatment. The electrochemistry of the two materials was evaluated in aqueous Zn-ion cells with 2 M ZnSO4 electrolyte using cyclic voltammetry, galvanostatic cycling, and rate capability testing. The thinner NVO(300) nanobelts (0.13 μm) demonstrate greater specific capacities and higher effective diffusion coefficients relative to the thicker NVO(500) nanorods. Notably however, while cells containing NVO(500) deliver lower specific capacity, they demonstrate enhanced capacity retention with cycling. The structural changes accompanying oxidation and reduction are elucidated via ex situ X-ray diffraction, transmission electron microscopy, and operando V K-edge X-ray absorption spectroscopy (XAS), where NVO material properties are shown to influence the ion insertion. Operando XAS verified that electron transfer corresponds directly to change in vanadium oxidation state, affirming vanadium redox as the governing electrochemical process.